Structural determinants in the bulk heterojunction. Issue 8 (7th February 2018) - Acocella, Angela; Höfinger, Siegfried; Haunschmid, Ernst; Pop, Sergiu C.; Narumi, Tetsu; Yasuoka, Kenji; Yasui, Masato; Zerbetto, Francesco
Abstract : A multiscale approach is used to characterize essential morphological features of the bulk heterojunction. Abstract : Photovoltaics is one of the key areas in renewable energy research with remarkable progress made every year. Here we consider the case of a photoactive material and study its structural composition and the resulting consequences for the fundamental processes driving solar energy conversion. A multiscale approach is used to characterize essential molecular properties of the light-absorbing layer. A selection of bulk-representative pairs of donor/acceptor molecules is extracted from the molecular dynamics simulation of the bulk heterojunction and analyzed at increasing levels of detail. Significantly increased ground state energies together with an array of additional structural characteristics are identified that all point towards an auxiliary role of the material's structural organization in mediating charge-transfer and -separation. Mechanistic studies of the type presented here can provide important insights into fundamental principles governing solar energy conversion in next-generation photovoltaic devices.